Angiotensin-converting enzyme inhibitory activity of some Vietnamese medicinal plants - Xoan Thi Le; Xuyen Thi Phi; Duong Thi Thuy Nguyen; Hang Thi Nguyet Pham; Tai Nguyen Van; Olapoju Samuel O.; Kinzo Matsumoto (Vietnam Journal of Science, Technology and Engineering, 2020)
This study investigated the angiotensin 1-converting enzyme (ACE) inhibitory activity of certain medicinal plants that have been traditionally used as an antihypertensive, diuretic, or related diseases treatment in Vietnam. Ten different medicinal plants were selected and screened for in vitro ACE inhibitory activity. A spectrophotometric assay was developed for the determination of ACE activity in the presence of ACE inhibitors using hippuryl-L-histidyl-L-leucine as the ACE-specific substrate. When the in vitro activities of ACE were assessed in the presence and absence of aqueous or ethanol extracts from each medicinal plant, 2 out of the 22 medicinal plant extracts inhibited the ACE activity by more than 90% at a concentration of 50 µg/ml. The estimated IC50 value of the L. rubra and U. sessilifructus were 1.31±0.44 and 12.86 µg/ml, respectively. These results suggest that the L. rubra rhizome and U. sessilifructus extract are potential antihypertensive drug-like candidates with ACE inhibitory activity.